Distribution of attacked plants along trails in leaf-cuttiog ants (Hymeooptera: Formicidae): consequences in territorial strategies - Farji Brener, Alejandro G (1993)
Leaf-cutting ants generally abandon plans before they are completely defoliated, following tbe intraspecifi.c leaf quality variation among and witbin plans. One Atta cephalotes nest was studied to determine tbe traíl roIation consequences in the territorial defense development. We supposed tblll, as a resolt of changes in the h arvest activity and trail use,leafcutting anu obtain a good and unpredictable coverage f:4 tbe foraging area. The study wu conducted in Barro Colorado Island, Panamá, in October, 1989. During seven sampling days we registered nomber, distance and orientation oí IIlUckedlabandoned trees and new/abandoned trails. The resulu suggest a large and unpredictable covering f:4 tbe foraging area as a consequence of roIational barvest activity. Since botb, planu and colony are sessile, advantages of donrinating a large foraging area are discussed